THE EFFECT OF COMPENSATION ON EMPLOYEE PERFORMANCE AT PT JOYCI NUSANTARA CEMERLANG - Nandita Melta Daughter; Fitria Lilyana; Nurhaeni Sikki (PT. Altin Riset Publishing, 2026)
PT Joyci Nusantara Cemerlang is a company engaged in the food industry, specifically in the production of dry cookies. In its production process, employees play an important role in maintaining product quality and ensuring smooth operations. However, based on pre-survey results and interviews, it was found that the compensation received by employees did not fully meet the Bandung Regency Minimum Wage Standard, along with a decline in performance in several aspects. This study aims to analyze the effect of compensation on employee performance. The research method used is a qualitative approach quantified into quantitative data. Data were collected through questionnaires distributed to 50 respondents and analyzed using descriptive analysis, simple linear regression test, correlation coefficient, determination, and t-test. The results show that compensation falls into the “Fair” category with an average score of 3.02, while employee performance is also in the “Fair” category with an average score of 3.19. Partially, compensation has an effect on employee performance with a t-value of 4.537 > t-table value of 1.677 and a significance level of 0.000. The coefficient of determination (R²) of 0.300 indicates that compensation contributes 30% to employee performance, while the remaining 70% is influenced by other factors not examined in this study.